Study of the Differences between Current and Favorite Organizational Culture from the View of Employees of Governmental Daily Rehabilitation Centers of Tehran - Marjan Mohammad-Zadeh; Ali Chabok; Mohammad Mousavi-Khattat; Iravan Masoudi-Asl; Masoud Karimlou (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: The main aim of this study is to compare differences between current and desirable organizational culture from the View of employees of governmental daily rehabilitation centers of Tehran. Materials & Methods: In this cross-sectional and comparative study, 116 employees of governmental daily rehabilitation centers of Tehran Who had at least diploma degree and 4 years of professional experience and were present at centers at the time of study were selected conveniently. Data has gathered via researcher made two sectional questionnaire. Content validity has approved and reliability has evaluated with test-retest method (r=0.835). Data were analyzed with t-test. Results: Total means for available and desirable organizational culture were 119.16 and 73.33 respectively indicating significant difference (p<0.001) While means of control factor were 8.77 and 9.00 respectively, and difference wasn't significant difference between current and favorite organizational culture regarding the control factor. In all of nine other factors differences were significant (P<0.001). Conclusion: Regarding significant difference between available and desirable organizational culture in the daily rehabilitation centers of Tehran, improving organizational culture in these centers seems to be essential. Considerable attention of authorities to this issue could be helpful in promoting service delivery efficiently and quality.